SEMIGROUP IDEALS AND PERMUTING 3-GENERALIZED DERIVATIONS IN PRIME NEAR RINGS - Ali, Asma; Atteya, Mehsin Jabel; Miyan, Phool; Ali, Farhat (Italian Journal of Pure and Applied Mathematics, 2015)
The purpose of the present paper is to prove some commutativity theorems in the setting of a semigroup ideal of a 3-prime near ring admitting a permuting generalized 3-derivation, thereby extending some known results of derivations, biderivations and 3-derivations.